Lived Experiences of Borderland Communities in Zimbabwe Livelihoods, Conservation, War and Covid-19 - Pophiwa, Nedson; Matanzima, Joshua; Helliker, Kirk. (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book examines the national borders and borderlands of Zimbabwe through the presentation of empirically rich case studies. It delves into the lived experiences, both past and present, of populations residing along the borders between Zimbabwe and its neighbours, i.e., Zambia, Botswana, South Africa and Mozambique. It locates these lived experiences within the political economy of Zimbabwe, and highlights a wide range of themes pertinent to borders, including health, COVID-19, marginalisation, resource access, conservation, human-wildlife conflicts, civil wars, politico-economic crises, border jumping and cross border trade. The borderland communities discussed also include ethnic minorities such as the Tonga, San, Ndau, Shangane, and Kalanga. Overall, the book demonstrates the centrality of borders to the Zimbabwean nation-state and the importance of reading history, politics and society from the borderlands. The book fits into the wider prevailing literature of border and borderlands in Africa and beyond and thus has appeal far beyond Zimbabwe. Its diverse themes also relate to topics covered in multiple disciplines, including history, anthropology, and sociology. Academics, development specialists and policy makers will benefit in different ways from the depth and breadth of the analysis in the book.
Chapter 1: The Lived Experiences of Zimbabwean Borderlands -- Chapter 2: Peasant Accumulation and Livelihoods Strategies in Zimbabwe's Mozambican Borderlands -- Chapter 3: Slippery Bananas? Environmental Conflicts, Banana Production and Entangled Livelihoods along the Zimbabwe-Mozambican border with specific reference to Honde Valley, 1992 - 2020 -- Chapter 4: Land Rights, Displacements and Rural Livelihoods in Zimbabwe's South-Eastern Borderlands -- Chapter 5: Borders, Boundaries, and Livelihoods in Western and North-Western Zimbabwe, 1890 - 2021 -- Chapter 6: Local Community Perceptions on Wildlife Conservation and Park-People Relationships in the Sengwe Area, Chiredzi District, Southeast Zimbabwe -- Chapter 7: Understanding the Complexities of Human Conflict Over Wildlife in the Border Town of Kariba, Zimbabwe -- Chapter 8: The Nexus between the Zimbabwe's Borderlands, Marginalised Peoples, Community Archiving and Archival Activism 4 -- Chapter 9: Entangled Borderlands: Effects of the 1978-1992 Mozambican Civil War on Border Communities in Zimbabwe -- Chapter 10: "Across the border, you are treated well, they care:" Patients, Travels and Therapeutic Mobilities in Honde Valley and Kariba Borderlands -- Chapter 11: The Covid-19 Pandemic and Tourism in Kariba Border Town -- Chapter 12: The Health Seeking Behaviour of Borderline Communities: The Status of the San People of Tsholotsho, Zimbabwe -- Chapter 13: Unfolding Realities of Urbanism at the Margins: Beitbridge (Zimbabwe) and Musina (South Africa) Border Towns as a Single Urban Frontier.
Keywords: Urban policy; Human geography; Cultural geography; Cultural property; Urban Policy; Social and Cultural Geography; Cultural Heritage